Wollastonite-magnesium hydroxide composite modified powder, and preparation method and application thereof

CN122941208APending Publication Date: 2026-10-20JIANGXI GUANGYUAN CHEM +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611124730.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]有鉴于此,本发明提供了一种针状硅灰石-氢氧化镁复合改性粉体及其制备方法与应用,以解决现有技术中难以在低填充量下同时实现材料的高阻燃性能与高力学性能的问题

Benefits of technology

1、本发明以针状硅灰石为刚性骨架、纳米氢氧化镁为阻燃组分、复合改性剂为界面调控单元,通过湿法机械复合-表面包覆工艺,构建了“刚性支撑-高效阻燃-界面相容”的多功能体系。该设计解决了单一粉体在阻燃、增强、抑烟方面难以兼顾的瓶颈,实现了阻燃、增强、抑烟性能的同步提升,为高端高分子材料提供了低成本、高性能化的高效解决方案;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention belongs to the field of composite material technology and provides a acicular wollastonite-magnesium hydroxide composite modified powder, its preparation method, and its application. The invention involves pretreating acicular wollastonite and nano-magnesium hydroxide separately; then mixing the pretreated acicular wollastonite slurry, pretreated nano-magnesium hydroxide, and a dispersant to obtain a mixed slurry; finally, mixing the mixed slurry, a composite modifier, and a pH adjuster, and reacting the mixture to obtain the acicular wollastonite-magnesium hydroxide composite modified powder. This method is simple, environmentally friendly, and low-cost. Using acicular wollastonite as a rigid framework, nano-magnesium hydroxide as a flame-retardant component, and the composite modifier as an interface control unit, a multifunctional system of rigid support, high-efficiency flame retardancy, and interfacial compatibility is constructed through a wet mechanical composite-surface coating process. This achieves simultaneous improvement in the flame retardant, reinforcing, and smoke-suppressing properties of the material at low filler content, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material modification technology, and in particular to a needle-shaped wollastonite-magnesium hydroxide composite modified powder, its preparation method and application. Background Technology

[0002] Needle-shaped wollastonite, with its unique needle-like crystal structure, high rigidity, and low oil absorption value, is often used as a reinforcing filler in materials such as plastics, rubber, and cables to improve the mechanical strength and dimensional stability of the products. Magnesium hydroxide, on the other hand, is an environmentally friendly inorganic flame retardant that exerts its flame-retardant and smoke-suppressing effects through endothermic decomposition and is widely used in the field of low-smoke halogen-free flame-retardant cables.

[0003] However, both types of powders have significant limitations when used alone: ​​on the one hand, needle-shaped wollastonite has a strong hydrophilic surface and poor compatibility with hydrophobic polymer matrices, which can only improve rigidity but cannot impart flame retardant function, and it is prone to agglomeration, resulting in a decrease in material toughness; on the other hand, magnesium hydroxide requires a high filling amount to achieve the expected flame retardant level, but excessive filling will seriously damage the mechanical properties of cable materials, such as reducing the elongation at break by more than 30%.

[0004] To balance flame retardancy and enhanced performance, attempts have been made to use a simple physical mixture of the two powders. However, existing composite methods lack effective control over the interfacial interactions between the powders, resulting in insufficient synergistic effect between wollastonite and magnesium hydroxide, making it difficult to simultaneously optimize flame retardancy and enhanced performance.

[0005] Therefore, it is of great significance to develop a needle-shaped wollastonite-magnesium hydroxide composite modified powder that can simultaneously improve the flame retardant and mechanical properties of materials with low filling amounts and its preparation method. Summary of the Invention

[0006] In view of this, the present invention provides a needle-shaped wollastonite-magnesium hydroxide composite modified powder, its preparation method and application, to solve the problem in the prior art that it is difficult to achieve both high flame retardant properties and high mechanical properties of materials with low filling amount at the same time.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder, comprising the following steps: 1) Pre-treat acicular wollastonite and nano-magnesium hydroxide respectively to obtain pre-treated acicular wollastonite and pre-treated nano-magnesium hydroxide; 2) The pretreated needle-shaped wollastonite slurry, pretreated nano-magnesium hydroxide, and dispersant are mixed to obtain a mixed slurry; 3) Mix the slurry, composite modifier and pH adjuster, and react to obtain needle-shaped wollastonite-magnesium hydroxide composite modified powder.

[0008] Preferably, the composite modifier is obtained by mixing a silane coupling agent, an aluminate coupling agent, and an organic solvent; the mass ratio of the silane coupling agent to the aluminate coupling agent is 1:2~3; and the total mass concentration of the silane coupling agent and the aluminate coupling agent in the composite modifier is 10~15%.

[0009] Preferably, the silane coupling agent includes one or more of KH-570 vinyl silane coupling agent, KH-550 amino silane coupling agent, and KH-560 epoxy silane coupling agent; the aluminate coupling agent includes one or more of DL-411 isopropoxy aluminate coupling agent, DL-402 aluminate coupling agent, and DL-409 stearoyl aluminate coupling agent; and the organic solvent includes one or more of anhydrous ethanol, isopropanol, and n-butanol.

[0010] Preferably, the pretreatment of the acicular wollastonite in step 1) includes: drying the acicular wollastonite at 100~120℃ for 5~7 h; the pretreatment of the nano magnesium hydroxide includes: drying the nano magnesium hydroxide at 70~90℃ for 3~5 h.

[0011] Preferably, the acicular wollastonite described in step 1) has a CaSiO3 content ≥98%, an aspect ratio of 10~20:1, and a particle size D. 50 The particle size is 3~5 μm; the Mg(OH)2 content of the nano-magnesium hydroxide is ≥99%, and the particle size D is 3~5 μm. 50 The wavelength is 50~100 nm.

[0012] Preferably, the slurry of the pretreated acicular wollastonite in step 2) is obtained by mixing the pretreated acicular wollastonite and water; the mass concentration of the slurry is 25~35%; the mass ratio of the pretreated nano magnesium hydroxide, dispersant and pretreated acicular wollastonite is 0.43~0.67:0.002~0.004:1.

[0013] Preferably, the mixing speed in step 2) is 1500~2000 r / min, the ultrasonic power is 300~500 W, and the time is 60 min.

[0014] Preferably, the dispersant in step 2) includes one or more of sodium pyrophosphate, sodium hexametaphosphate, and sodium polyacrylate.

[0015] Preferably, in step 3), the mass ratio of the composite modifier to the total mass of pretreated needle-shaped wollastonite and pretreated nano-magnesium hydroxide in the mixed slurry is 0.015~0.025:1; the amount of pH adjuster used is to make the pH of the reaction system 6~7.

[0016] Preferably, the reaction temperature in step 3) is 60~70℃ and the time is 120~180 min.

[0017] Preferably, the pH adjuster in step 3) includes one or more of dilute hydrochloric acid, glacial acetic acid, ammonia, and triethanolamine.

[0018] The present invention also provides a needle-shaped wollastonite-magnesium hydroxide composite modified powder prepared by the above-mentioned preparation method of needle-shaped wollastonite-magnesium hydroxide composite modified powder.

[0019] The present invention also provides an application of the above-mentioned needle-shaped wollastonite-magnesium hydroxide composite modified powder in the preparation of low-smoke halogen-free flame-retardant cable materials, environmentally friendly coatings, flame-retardant plastics or rubber seals.

[0020] As can be seen from the above technical solution, compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses acicular wollastonite as a rigid framework, nano-magnesium hydroxide as a flame-retardant component, and a composite modifier as an interface control unit. Through a wet mechanical composite-surface coating process, a multifunctional system of "rigid support, high-efficiency flame retardancy, and interfacial compatibility" is constructed. This design solves the bottleneck of single powders being unable to simultaneously achieve flame retardancy, reinforcement, and smoke suppression, realizing the simultaneous improvement of flame retardancy, reinforcement, and smoke suppression performance, and providing a low-cost, high-performance, and efficient solution for high-end polymer materials. 2. The composite modifier used in the method of the present invention is used in small amounts, is environmentally friendly and non-toxic, and does not produce harmful gases; the process can be modified on the basis of existing inorganic powder modification production lines, the reaction conditions are mild, the production cost is reduced by 15-20% compared with single nano magnesium hydroxide, and it has the conditions for large-scale production. 3. The composite modified powder prepared by the method described in this invention has a wide range of applications, especially suitable for high-end polymer materials with high mechanical and flame retardant requirements. In low-smoke halogen-free flame-retardant cable materials, the composite modified powder requires a small filling amount. When the filling amount is only 60 parts, the oxygen index of the low-smoke halogen-free flame-retardant cable material can reach 36.5%, which is higher than the 35.2% of 65 parts of magnesium hydroxide alone; the tensile strength can reach 15.2 MPa, and the elongation at break can reach 292%; the maximum smoke density can be as low as 3.02, and the smoke density grade can reach 3.21; the specific gravity of the product is reduced to 1.45 g / cm³. 3 The following approach achieves synergistic optimization of the flame retardant and mechanical properties of materials with low filler content. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0022] Figure 1 This is a SEM image of the needle-shaped wollastonite-magnesium hydroxide composite modified powder prepared in Example 1 of the present invention. Detailed Implementation

[0023] This invention provides a method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder, comprising the following steps: 1) Pre-treat acicular wollastonite and nano-magnesium hydroxide respectively to obtain pre-treated acicular wollastonite and pre-treated nano-magnesium hydroxide; 2) The pretreated needle-shaped wollastonite slurry, pretreated nano-magnesium hydroxide, and dispersant are mixed to obtain a mixed slurry; 3) Mix the slurry, composite modifier and pH adjuster, and react to obtain needle-shaped wollastonite-magnesium hydroxide composite modified powder.

[0024] In this invention, the composite modifier is obtained by mixing a silane coupling agent, an aluminate coupling agent, and an organic solvent; the mass ratio of the silane coupling agent to the aluminate coupling agent is preferably 1:2~3, more preferably 1:2.2~2.8, and even more preferably 1:2.3~2.5; the total mass concentration of the silane coupling agent and the aluminate coupling agent in the composite modifier is preferably 10~15%, more preferably 12~14%, and even more preferably 13%.

[0025] In this invention, the silane coupling agent preferably includes one or more of KH-570 vinyl silane coupling agent, KH-550 amino silane coupling agent, and KH-560 epoxy silane coupling agent; the aluminate coupling agent preferably includes one or more of DL-411 isopropoxy aluminate coupling agent, DL-402 aluminate coupling agent, and DL-409 stearoyl aluminate coupling agent; and the organic solvent preferably includes one or more of anhydrous ethanol, isopropanol, and n-butanol.

[0026] In this invention, the pretreatment of the acicular wollastonite in step 1) includes: drying the acicular wollastonite at 100~120℃ for 5~7 h to remove surface adsorbed water; the drying temperature is preferably 105~115℃, more preferably 110℃; the drying time is preferably 5.5~6.5 h, more preferably 6 h.

[0027] In this invention, the pretreatment of nano-magnesium hydroxide in step 1) includes: drying nano-magnesium hydroxide at 70~90℃ for 3~5 h; the drying temperature is preferably 75~85℃, more preferably 80℃; the drying time is preferably 3.5~4.5 h, more preferably 4 h.

[0028] In this invention, the CaSiO3 content of the acicular wollastonite in step 1) is ≥98%, preferably 98.5~99.5%, more preferably 98.6~99.2%, and even more preferably 98.8~99%; the aspect ratio of the acicular wollastonite is 10~20:1, preferably 12~18:1, more preferably 13~16:1, and even more preferably 15:1; the particle size D of the acicular wollastonite is... 50 The particle size is 3~5 μm, preferably 3.2~4.8 μm, more preferably 3.5~4.5 μm, and even more preferably 4 μm; the Mg(OH)2 content of the nano-magnesium hydroxide is ≥99%, preferably 99.2~99.9%, more preferably 99.3~99.8%, and even more preferably 99.5~99.7%; the particle size D of the nano-magnesium hydroxide is... 50 The nm value is 50~100 nm, preferably 60~90 nm, more preferably 65~85 nm, and even more preferably 70~80 nm.

[0029] In this invention, the slurry of pretreated acicular wollastonite in step 2) is obtained by mixing pretreated acicular wollastonite and water; the mass concentration of the slurry is 25-35%, preferably 26-33%, more preferably 28-32%, and even more preferably 30%; the mass ratio of pretreated nano-magnesium hydroxide, dispersant and pretreated acicular wollastonite is 0.43-0.67:0.002-0.004:1, preferably 0.45-0.65:0.0022-0.0038:1, more preferably 0.48-0.6:0.0025-0.0035:1, and even more preferably 0.5-0.55:0.0028-0.003:1.

[0030] In this invention, the mixing in step 2) is preferably done by first premixing the pretreated needle-shaped wollastonite slurry with a dispersant, and then adding nano-magnesium hydroxide for mixing.

[0031] In this invention, the premixing speed is preferably 1500~2000 r / min, more preferably 1600~1800 r / min, and even more preferably 1700 r / min; the premixing time is preferably 20~40 min, more preferably 25~35 min, and even more preferably 30 min.

[0032] In this invention, the mixing speed in step 2) is 1500~2000 r / min, preferably 1600~1800 r / min, more preferably 1700 r / min; the ultrasonic power of the mixing is 300~500 W, preferably 320~480 W, more preferably 350~450 W, more preferably 400 W; the mixing time is 50~70 min, more preferably 55~65 min, more preferably 60 min.

[0033] In this invention, ultrasonic-assisted dispersion is used in the mixing process described in step 2), which enables nano-magnesium hydroxide to be uniformly loaded on the surface and interstices of acicular wollastonite.

[0034] In this invention, the dispersant in step 2) preferably includes one or more of sodium pyrophosphate, sodium hexametaphosphate, and sodium polyacrylate.

[0035] In this invention, the mass ratio of the composite modifier in step 3) to the total mass of pretreated needle-shaped wollastonite and pretreated nano-magnesium hydroxide in the mixed slurry is 0.015~0.025:1, preferably 0.016~0.022:1, more preferably 0.018~0.02:1; the amount of pH adjuster used is to make the pH value of the reaction system 6~7, preferably 6.2~6.8, more preferably 6.5.

[0036] In this invention, the reaction temperature in step 3) is 60~70℃, preferably 62~68℃, more preferably 65℃; the reaction time is 120~180 min, preferably 130~160 min, more preferably 150 min; this reaction enables the composite modifier molecules to be coated on the surface of the powder in the mixed slurry through chemical bonding and physical adsorption.

[0037] In this invention, the pH adjuster mentioned in step 3) preferably includes one or more of dilute hydrochloric acid, glacial acetic acid, ammonia, and triethanolamine, and more preferably a mixed solution of glacial acetic acid and ammonia.

[0038] In this invention, the reaction described in step 3) is preferably followed by sequential operations of pressure filtration, washing, and drying; the washing endpoint is preferably such that the conductivity of the washed filtrate is ≤10 μS / cm, more preferably 3~9 μS / cm, and even more preferably 5~8 μS / cm; the drying temperature is preferably 105~115℃, more preferably 108~112℃, and even more preferably 110℃; the drying time is preferably 10~12 h, more preferably 10.5~11.5 h, and even more preferably 11 h.

[0039] In this invention, the structure of the needle-shaped wollastonite-magnesium hydroxide composite modified powder is preferably a composite structure in which nano-magnesium hydroxide is loaded on the surface of needle-shaped wollastonite and coated with a composite modifier layer.

[0040] In this invention, acicular wollastonite is used as a rigid framework, which can significantly improve the tensile strength and dimensional stability of the material. Nano-magnesium hydroxide is loaded on the surface of acicular wollastonite to form a continuous flame-retardant barrier and reduce the amount of flame-retardant filler. Composite modifiers synergistically regulate the interface to solve the compatibility problem between acicular wollastonite and nano-magnesium hydroxide and polymer matrix, and achieve simultaneous optimization of reinforcement and flame retardancy.

[0041] The present invention also provides a needle-shaped wollastonite-magnesium hydroxide composite modified powder prepared by the above-mentioned preparation method of needle-shaped wollastonite-magnesium hydroxide composite modified powder.

[0042] The present invention also provides an application of the above-mentioned needle-shaped wollastonite-magnesium hydroxide composite modified powder in the preparation of low-smoke halogen-free flame-retardant cable materials, environmentally friendly coatings, flame-retardant plastics or rubber seals.

[0043] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] Example 1

[0045] Preparation of needle-shaped wollastonite-magnesium hydroxide composite modified powder: 1) Acicular wollastonite (CaSiO3 content 98.6%, aspect ratio 15:1, particle size D) 50 =4 μm) was dried at 110℃ for 6 h, while nano-magnesium hydroxide (Mg(OH)2 content of 99.2%, particle size D) was dried. 50 =80nm) was vacuum dried at 80℃ for 4 h to obtain dried needle-shaped wollastonite and dried nano-magnesium hydroxide; 2) Mix 100 kg of dried needle-shaped wollastonite with 286 kg of deionized water to obtain a slurry with a mass concentration of 30%. Then, stir the slurry with 0.3 kg of sodium pyrophosphate at a high speed of 1800 r / min for 30 min. Then, add 53.8 kg of dried nano-magnesium hydroxide (where the mass ratio of dried nano-magnesium hydroxide to dried needle-shaped wollastonite is 0.538:1) and continue stirring at a high speed of 1800 r / min for 60 min. At the same time, turn on the 400 W ultrasonic-assisted dispersion to obtain a mixed slurry. 3) Mix silane coupling agent KH-570 and aluminate coupling agent DL-411 at a mass ratio of 1:2.5, and dilute with anhydrous ethanol to a mass concentration of 12% to obtain a composite modifier; heat the mixed slurry to 65℃, add 3.1 kg of the above composite modifier dropwise, and add glacial acetic acid to make the pH of the reaction system 6.5 and react for 150 min. Then filter and wash until the conductivity of the filtrate is 8 μS / cm, and then vacuum dry at 110℃ for 11 h. Finally, obtain needle-shaped wollastonite-magnesium hydroxide composite modified powder by air jet pulverization.

[0046] Preparation of low-smoke halogen-free flame-retardant cable materials: 60 kg of needle-shaped wollastonite-magnesium hydroxide composite modified powder, 15 kg of EVA, 10 kg of POE, 10 kg of LLPE, 6 kg of MC218 compatibilizer, and 0.7 kg of silicone masterbatch prepared in Example 1 were mixed, kneaded at 150°C for 30 min, open-milled at 150°C for 3 min, and finally pressed into sheets at 170°C and 10 MPa for 10 min, and then cold-pressed at room temperature for 5 min to fix the material, thus obtaining low-smoke halogen-free flame-retardant cable material.

[0047] The scanning electron microscope (SEM) image of the needle-shaped wollastonite-magnesium hydroxide composite modified powder prepared in Example 1 is shown below. Figure 1 As shown; from Figure 1 As can be seen from the image, the morphology of needle-like wollastonite coated with nano-magnesium hydroxide in the composite modified powder prepared in Example 1 is shown.

[0048] The flame retardant properties, mechanical properties, smoke density properties, and specific gravity of the low-smoke halogen-free flame-retardant cable material prepared in Example 1 were tested. The flame retardant properties were tested according to GB / T 2406.2-2009 for the oxygen index and GB / T 2408-2021 for the UL94 vertical flammability rating. The mechanical properties were tested according to GB / T1040.3-2006 for tensile strength and elongation at break. The smoke density was tested according to GB / T8323.2-2022. The specific gravity was tested using the water displacement method according to GB / T 1033.1-2021. The flame retardant performance test results are as follows: oxygen index 36.5%, reaching UL94 V-0 rating; mechanical property test results are as follows: tensile strength 14.8 MPa, elongation at break 285%; smoke density test results are as follows: maximum smoke density 3.02, smoke density rating 3.21; specific gravity 1.447 g / cm³. 3 .

[0049] Example 2

[0050] The only difference between Example 2 and Example 1 is that the mass ratio of dried nano-magnesium hydroxide to dried needle-shaped wollastonite in step 2) is set to 0.43:1, while other conditions remain unchanged. The preparation conditions of the low-smoke halogen-free flame-retardant cable material also remain unchanged, thus obtaining needle-shaped wollastonite-magnesium hydroxide composite modified powder and low-smoke halogen-free flame-retardant cable material.

[0051] The flame retardant properties, mechanical properties, smoke density properties, and specific gravity of the low-smoke halogen-free flame retardant cable material prepared in Example 2 were tested using the same testing methods as in Example 1.

[0052] The flame retardant performance test results are as follows: oxygen index 35.8%; mechanical property test results are as follows: tensile strength 15.2 MPa, elongation at break 292%; smoke density performance test results are as follows: maximum smoke density 3.15, smoke density rating 3.34; specific gravity 1.432 g / cm³. 3 The results show that increasing the proportion of acicular wollastonite improves mechanical strength but slightly reduces flame retardant properties; the composite ratio can be adjusted according to actual needs.

[0053] Comparative Example 1

[0054] Low-smoke, halogen-free flame-retardant cable material is prepared directly using nano-magnesium hydroxide. The specific preparation method is as follows: 65 kg of nano magnesium hydroxide, 15 kg of EVA, 10 kg of POE, 10 kg of LLPE, 6 kg of MC218 compatibilizer, and 0.7 kg of silicone masterbatch were mixed, kneaded at 150°C for 30 min, open-milled at 150°C for 3 min, and finally pressed into sheets at 170°C and 10 MPa for 10 min, and then cold-pressed at room temperature for 5 min to fix the material, thus obtaining low-smoke halogen-free flame-retardant cable material.

[0055] The flame retardant properties, mechanical properties, and smoke density properties of the low-smoke halogen-free flame retardant cable material prepared in Comparative Example 1 were tested using the same testing methods as in Example 1.

[0056] The flame retardant performance test results are as follows: oxygen index is 35.2%; the mechanical performance test results are as follows: tensile strength is 12.1 MPa, elongation at break is 240%; the smoke density performance test results are as follows: maximum smoke density is 4.17, smoke density grade is 4.24.

[0057] Comparative Example 2

[0058] The only difference between Comparative Example 2 and Example 2 is that the low-smoke, halogen-free flame-retardant cable material was prepared by directly physically mixing acicular wollastonite and nano-magnesium hydroxide, without modifying the acicular wollastonite-magnesium hydroxide composite powder. The specific preparation method is as follows: Dry nano-magnesium hydroxide (same as in Example 2) and dry acicular wollastonite (same as in Example 2) were mixed at a mass ratio of 0.43:1 to obtain acicular wollastonite-magnesium hydroxide composite powder. 60 kg of the acicular wollastonite-magnesium hydroxide composite powder, 15 kg of EVA, 10 kg of POE, 10 kg of LLPE, 6 kg of MC218 compatibilizer, and 0.7 kg of silicone masterbatch were mixed, subjected to intensive kneading at 150°C for 30 min, open kneading at 150°C for 3 min, and finally pressed into sheets at 170°C and 10 MPa for 10 min, followed by cold pressing at room temperature for 5 min to obtain low-smoke halogen-free flame-retardant cable material.

[0059] The flame retardant properties, mechanical properties, and smoke density properties of the low-smoke halogen-free flame retardant cable material prepared in Comparative Example 2 were tested using the same testing methods as in Example 1.

[0060] The flame retardant performance test results were as follows: oxygen index 34.5%; mechanical property test results were as follows: tensile strength 11.8 MPa, elongation at break 225%; smoke density test results were as follows: maximum smoke density 4.31. The results indicate that, compared with Example 2 of this invention, the flame retardant, mechanical, and smoke suppression properties of the low-smoke halogen-free flame-retardant cable material prepared in this comparative example are significantly worse, fully demonstrating that the composite modification design described in this invention can synergistically improve the flame retardant, mechanical, and smoke suppression properties of the low-smoke halogen-free flame-retardant cable material.

[0061] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder, characterized in that, Includes the following steps: 1) Pre-treat acicular wollastonite and nano-magnesium hydroxide respectively to obtain pre-treated acicular wollastonite and pre-treated nano-magnesium hydroxide; 2) The pretreated needle-shaped wollastonite slurry, pretreated nano-magnesium hydroxide, and dispersant are mixed to obtain a mixed slurry; 3) Mix the slurry, composite modifier and pH adjuster, and react to obtain needle-shaped wollastonite-magnesium hydroxide composite modified powder; The composite modifier is obtained by mixing a silane coupling agent, an aluminate coupling agent, and an organic solvent; the mass ratio of the silane coupling agent to the aluminate coupling agent is 1:2~3; and the total mass concentration of the silane coupling agent and the aluminate coupling agent in the composite modifier is 10~15%.

2. The method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 1, characterized in that, The silane coupling agent includes one or more of KH-570 vinyl silane coupling agent, KH-550 amino silane coupling agent, and KH-560 epoxy silane coupling agent. The aluminate coupling agent includes one or more of DL-411 isopropoxy aluminate coupling agent, DL-402 aluminate coupling agent, and DL-409 stearoyl aluminate coupling agent. The organic solvent includes one or more of anhydrous ethanol, isopropanol, and n-butanol.

3. The method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 2, characterized in that, The pretreatment of acicular wollastonite in step 1) includes drying the acicular wollastonite at 100~120℃ for 5~7 h; The pretreatment of the nano-magnesium hydroxide includes drying the nano-magnesium hydroxide at 70~90℃ for 3~5 h; The acicular wollastonite described in step 1) has a CaSiO3 content ≥98%, an aspect ratio of 10~20:1, and a particle size D. 50 3~5 μm; The nano-magnesium hydroxide has a Mg(OH)₂ content ≥99% and a particle size D. 50 The wavelength is 50~100 nm.

4. A method for preparing a needle-shaped wollastonite-magnesium hydroxide composite modified powder according to any one of claims 1 to 3, characterized in that, The slurry of pretreated acicular wollastonite in step 2) is obtained by mixing pretreated acicular wollastonite with water; the mass concentration of the slurry is 25-35%. The mass ratio of the pretreated nano-magnesium hydroxide, dispersant and pretreated acicular wollastonite is 0.43~0.67:0.002~0.004:

1.

5. The method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 4, characterized in that, In step 2), the mixing speed is 1500~2000 r / min, the ultrasonic power is 300~500 W, and the time is 60 min.

6. The method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 5, characterized in that, The dispersant mentioned in step 2) includes one or more of sodium pyrophosphate, sodium hexametaphosphate, and sodium polyacrylate.

7. The method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 6, characterized in that, The mass ratio of the composite modifier mentioned in step 3) to the total mass of pretreated acicular wollastonite and pretreated nano-magnesium hydroxide in the mixed slurry is 0.015~0.025:1; The amount of pH adjuster used is such that the pH of the reaction system is 6-7; The reaction in step 3) is carried out at a temperature of 60-70°C for 120-180 min.

8. The method for preparing needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 7, characterized in that, The pH adjuster mentioned in step 3) includes one or more of dilute hydrochloric acid, glacial acetic acid, ammonia, and triethanolamine.

9. The acicular wollastonite-magnesium hydroxide composite modified powder prepared by the method for preparing acicular wollastonite-magnesium hydroxide composite modified powder according to any one of claims 1 to 8.

10. The application of the needle-shaped wollastonite-magnesium hydroxide composite modified powder according to claim 9 in the preparation of low-smoke halogen-free flame-retardant cable materials, environmentally friendly coatings, flame-retardant plastics or rubber seals.